Distribution transformer losses evaluation under non-linear load - Mat Said, Dalila (2009)
Harmonic effect on power system component and load are one of the important considerations when evaluating the impact of harmonics. Transformers are one of the component and usually the interface between the supply and most nonlinear load. With the increasing use of nonlinear load the harmonic problem become worse. The increased losses in the transformer due to the harmonic distortion can cause excessive winding loss and abnormal temperature rise. This paper presents the analysis and evaluation of distribution transformer losses under non-linear load. In this study the harmonic data logging was conducted in the commercial building and the losses caused by harmonic in distribution transformer were calculated. The life of the transformer also can be estimated from the simulation results. The results show that an increase in the current harmonic distortion will increase the transformer losses and hence decreased it life expectancy.